Impact of Myo-Inositol on Ovary and Menstrual Cycle in Polycystic Ovarian Syndrome (PCOS) - A Therapeutic Approach - Rozina Khatoon; Habiba Sharaf Ali; Ome Kulsoom; Mehreen Yousaf Rana; Monika Maheshwari (ziauddin University, 2024)
Background: Women of reproductive age develop menstrual irregularities along with infertility because of polycystic ovary syndrome (PCOS); the most common endocrine disorder. Myo-inositol (MI) is found to have a proven role in the treatment of this disorder.  The objective of this study was to determine the efficacy of Myo-inositol in regulating the menstrual cycle in women with PCOS. Methods: The study was conducted in 2019 at the Obstetrics and Gynecology Department of a tertiary care hospital with a sample of 50 women aged 18-45 years, having PCOS diagnosed with complaints of irregular menstrual cycles. Women with ovulatory dysfunction were excluded. Myo-inositol was given as 2 gm/day for 3 months. Pre- and post-trial data were collected, compared and analyzed through SPSS version 23 and a p-value <0.05 was considered statistically significant. Results: Mean±SD age of participant women was 27.68 ± 4.787 years. The menstrual cycle duration increased from Mean±SD 4.36 ± 2.22 to 4.70 ± 1.51 days after treatment with MI. The cycle flow increased from 19.10 ± 37.92 to 14.12 ± 13.34 ml (p-value < 0.001 each). Right and left ovary volume also decreased (p-value < 0.001 each) post-treatment. There were significant improvements in cycle flow severity towards normal pattern (from 14% to 80%; p-value < 0.001). The efficacy of Myo-inositol in regulating menstrual flow severity increased with decreasing age (p-value = <0.0001). Conclusion: Myo-Inositol was found efficacious in the treatment of PCOS and corrects menstrual irregularities, and menstrual flow, and normalizes ovarian volumes. Keywords: Inositol; Polycystic Ovary Syndrome (PCOS); Menstrual Irregularities; Myo-inositol.